ISOLATION AND IDENTIFICATION OF BIOFILM-FORMING BACTERIA IN FOODS SUPPLIED FOR CONSUMPTION IN OPEN-AIR MARKET STALLS: A CASE STUDY IN AYDIN PROVINCE - Mediha Onur; Esin Poyrazoğlu (Trakya University Journal of Natural Sciences, 2023)
In this study, the isolation and identification of bacteria that form biofilms on various food products sold on open-air market stalls in Aydın Province were aimed. Bacteria were isolated from food surfaces in aseptic conditions and isolated after incubation in the Tryptic Soy Agar medium at 37°C for 24-48 hours. DNA isolations of the isolated bacteria were performed and the PCR products obtained were used for sequencing. The Congo Red Agar method was used to qualitatively analyze biofilm formation. According to this method, bacteria forming black colonies were evaluated as biofilm-positive and were subjected to quantitative analysis using the Microplate method. A total of 67 bacteria were isolated from the sampled food items, of which 7 were strong and 2 were moderate biofilm producers, showing that more importance should be given to food hygiene.